A Creative Inquiry Attempt in Architecture Education: Producing an “...ism” - Bengi, Sena Işıklar (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2026)
This study examines the pedagogical boundaries of freedom in architectural education through a student-centred and critical classroom experience. In the process structured on researcher student collaboration, students were positioned not merely as receivers of knowledge but as actors who generate value. The discussion, conducted around the question “What would postmodernism criticize if it emerged today?”, encompassed critiques ranging from class inequality to the urban skyline. The students’ proposals were compiled within the framework of problem definition, supporting arguments, and counterarguments. These proposals were evaluated in relation to the positioning of creativity against institutional, political, and technological boundaries; the relationship between spatial justice and design; and the balance between individual freedom and collective responsibility. The findings reveal the creative potential of free thought in architecture and demonstrate education as a field of polyphonic production. It is anticipated that the participating students’ recognition of architecture’s potential to transform the social and physical environment, as well as its intellectual dimensions, will have a lasting impact in helping them position their own roles within this transformation.